PELATIHAN PEMBELAJARAN DIFERENSIASI UNTUK MEMENUHI KEBUTUHAN BELAJAR SISWA SEKOLAH DASAR DALAM MERDEKA BELAJAR - Putri Rachmadyanti; Siti Ina Savira; Citra Fitri Kholidya; Evi Winingsih; Dewi Komalasari; Wulan Patria Saroinsong (FKIP Universitas Trilogi, 2024)
Title The diverse characteristics of students are a challenge for teachers to accommodate students' learning needs. This problem is also faced by teachers at SD Islam Kota Blitar. The problem faced by these teachers is to design learning that is able to meet the needs of the various characteristics of learning students, both regular and children with special needs. One strategy that can be used to achieve this in the era of Merdeka Belajar is Differentiation Learning. The purpose of this activity is to provide knowledge and skills in preparing Differentiated Learning Plan for Elementary School teachers. The expected target is 65% of the partners are very satisfied with the guidance that has been carried out by the Team. The data is described through satisfaction surveys and mentoring processes for teachers as training participants. The methods used in this training include providing contextual understanding of understanding student learning styles, learning media focused on student learning styles and learning differences. The training continued with hands-on practice of compiling lesson plans. This training was carried out attractively by observing health protocols. At the end of the activity, it was found that on average 86.755% of the partners were very satisfied with the guidance carried out by the Team. It is hoped that participants will be able to apply the skills they have acquired on an ongoing basis in class